Penerapan Algoritma C4.5 Untuk Klasifikasi Kepuasan Pelanggan Jasa Vidio Shotting Garasi Potret Purbalingga - Wiyanto Wiyanto; Anggit Prasetyo Utomo (Jurnal SIGMA, 2019)
At present there are many companies that set up businesses in the field of video shooting, one of which is the Purbalingga Portrait Garage. The increasingly fierce competition in today's business world requires employers to be quick and responsive in making decisions so that established companies can survive amid such situations and conditions. One method that can be used for this is the data mining algorithm C4.5 method. The advantages of using this decision tree classification model are that the results of the tree are simple and easy to understand. The learning and classification process is simple and fast. In general, the decision tree algorithm classification model has a high degree of accuracy. From the calculation of customer satisfaction data training data with C4.5 algorithm using training data with confusion matrix has a value that is accuracy of 90.00%, precision 86.98%, and recall 96.98% and ROC curve optimistic with excellent classification accuracy of 0.980. This shows that the results of this prediction can be used for new quality test data. From the analysis of training data obtained a decision tree that has 20 rule models that can be used as a reference in making satisfaction in portrait garage customers. Keywords : Satisfaction, Service, C4.5 Algorithm, Data mining, Decision Tree